What the Fall of Angels Tells Us about the Essence of Morality - Martyna Koszkało (MDPI AG, 2021)
The article describes two concepts of the sources of morality present in the evolutionist traditions (Evolution of Ethics and the Veneer Theory). Then, a modal argument against the evolutionist theory of morality is presented, based on the history of the fall of angels present in classical theism. This story is taken in the article as a possible example of the actions of individuals who operate outside of any evolutionary and social context, and of those whose ontic constitution excludes the possession of emotions. In this way, an attempt is made to present the essential features of anyone that is subject to moral evaluation, thus concluding that morality in its essence cannot be defined in biological and evolutionary terms.